Nível de conhecimento do cirurgião-dentista no diagnóstico diferencial da fluorose dentária - Souza, Maria de Fátima Azevedo (2007)
Increasing levels of dental fluorosis are a major concern to public health authorities. The ability to discriminate fluorosis from other enamel modifications is an important factor to support decision makers in epidemiology and oral health. The main objective of this research is to investigate the ability of the odontologists working for the public health services in Fortaleza, to discriminate fluorosis from other enamel alterations, the severity of the disease and the correct clinical approach. Two hundred dentists out of 527 professionals of the public health services answered a semi-structured survey, based on the evaluation of 20 digitalized pictures showing enamel modifications. The presence or absence of fluorosis, as well as the severity of the disease were determined according to the Dean’s index. We were unable to detect an effect of the school of graduation (p>0.05) on the ability to diagnose fluorosis. However, the youngest, less experienced dentists performed better (p<0.05) for both fluorosis diagnosis and to determine to adequate clinical approach for each case. Also, odontologists working in the city health services were more likely to get higher scores compared to the ones working for the state services, with an average of correct answers for differential diagnosis of 7.70 ± 0.15. Although a few subjects achieved less than 30% of correct answers, pictures displaying more severe cases of fluorosis were more likely to result in correctly answered questions. The vast majority (90%) of the subjects reported to have a poor ability do diagnose fluorosis, although 75% had received information about that disease during undergraduation. The odontologists also displayed a very poor performance (2,71 ± 0,76) in defining the best clinical approach, and about 70% of them asked for specific training for correctly diagnose dental fluorosis. Based on the above results, we conclude that most dental surgeons working for the public health services in Fortaleza displayed a poor knowledge about dental fluorosis and lack an adequate training to diagnose and treat that disease. Similar researchs in other regions of Ceara should be performed in order to better identify the deficiencies of the public health services, at different levels.